Acute pancreatitis in pregnancy: a challenge for the clinician - Miglani, Urvashi; Pahuja, Nikita; Laul, Poonam; Kadam, V. K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Acute pancreatitis is one of the very rare events in pregnancy associated with high maternal and fetal morbidity and mortality. We are presenting a case of acute pancreatitis in a 25 year old G2P1L1 at 33 weeks of gestation with previous LSCS who presented to us with hypertension, epigastric pain, vomiting. Investigations revealed hyperamylysemia, hypertriglyceridemia and deranged liver enzymes. After examination and investigations, diagnosis of acute pancreatitis with pregnancy was made. She underwent caesarean section for obstetric hemorrhage and was put in intensive care for 3 days. She was discharged after. 1 week and is under regular follow up for past 6 months.